Refrigeration technologies in food industries: a review - Kumar, Sanoj; Kumar, Pankaj (Journal of Postharvest Technology, 2017)
Refrigeration has become an essential part of the food chain. It is used in all stages of the chain, from food processing, to distribution, retail and final consumption in the home. The food industry employs both chilling and freezing processes where the food is cooled from ambient to temperatures above 0°C in the former and between -18°C and –35°C in the latter to slow the physical, microbiological and chemical activities that cause deterioration in foods. In these processes mechanical refrigeration technologies are invariably employed that contribute significantly to the environmental impacts of the food sector both through direct and indirect greenhouse gas emissions. To reduce these emissions, research and development worldwide is aimed at both improving the performance of conventional systems and the development of new refrigeration technologies of potentially much lower environmental impacts. This paper provides a brief review of both current state of the art technologies and emerging refrigeration technologies that have the potential to reduce the environmental impacts of refrigeration in the food industry. The paper also highlights research and development needs to accelerate the development and adoption of these technologies by the food sector.